Non-collagenous ECM proteins in blood vessel morphogenesis and cancer - Kostourou, Vassiliki; Papalazarou, Vassilis (Biochimica et biophysica acta, 2014)
The extracellular matrix (ECM) is constituted by diverse composite structures, which determine the specific to each organ, histological architecture and provides cells with biological information, mechanical support and a scaffold for adhesion and migration. The pleiotropic effects of the ECM stem from the dynamic changes in its molecular composition and the ability to remodel in order to effectively regulate biological outcomes. Besides collagens, fibronectin and laminin are two major fiber-forming constituents of various ECM structures. This review will focus on the properties and the biological functions of non-collagenous extracellular matrix especially on laminin and fibronectin that are currently emerging as important regulators of blood vessel formation and function in health and disease. The ECM is a fundamental component of the microenvironment of blood vessels, with activities extending beyond providing a vascular scaffold; extremely versatile it directly or indirectly modulates all essential cellular functions crucial for angiogenesis, including cell adhesion, migration, proliferation, differentiation and lumen formation. Specifically, fibronectin and laminins play decisive roles in blood vessel morphogenesis both during embryonic development and in pathological conditions, such as cancer. Emerging evidence demonstrates the importance of ECM function during embryonic development, organ formation and tissue homeostasis. A wealth of data also illustrates the crucial role of the ECM in several human pathophysiological processes, including fibrosis, skeletal diseases, vascular pathologies and cancer. Notably, several ECM components have been identified as potential therapeutic targets for various diseases, including cancer. This article is part of a Special Issue entitled Matrix-mediated cell behaviour and properties. [Display omitted] •Vascular basement membrane provides mechanical and chemical cues to regulate cell responses.•Vascular membrane structure varies in different organs and between angiogenic and quiescent vessels.•Laminins stabilize blood vessels whereas fibronectin is essential for blood vessel development.•Altered expression of laminin chains promotes cancer cell migration and invasion.•Increased fibronectin expression facilitates tumor growth and angiogenesis.